Publisher Correction: Sensory attenuation in Parkinson's disease is related to disease severity and dopamine dose. Issue 1 (December 2018) - Wolpe, Noham; Zhang, Jiaxiang; Nombela, Cristina; Ingram, James; Wolpert, Daniel; Rowe, James
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.